Absolute truths eaudiobook - Howatch, Susan (Church of England, 2008)
It is 1965, and Charles Ashworth has attained the plum position of bishop of Starbridge, an honor that keeps him in a heady whirl of activity that would exhaust the most seasoned corporate executive. With the invaluable support of his minions and his attractive, unsinkable wife, Ashworth stands against the amorality and decadence of the age—"Anti-Sex Ashworth." He slays his opponents by being a tough, efficient, confident churchman, the torments of his past long since dead and buried. But when Ashworth's beloved wife dies, a profound crisis of his faith begins unexpectedly and with brutal force. As bereavement overwhelms his spiritual equilibrium, suddenly Ashworth finds himself staring into the chasm of all the lies he's been telling himself for years: about his marriage, his children, even his views on the church. And as he suspects his old nemesis and dean, Neville Aysgarth, of drinking too much, of financial chicanery, of—God forbid—having an affair, Ashworth discovers to his horror that he is tempted to commit the very acts that he has so publicly denounced. Spiraling downwards, Ashworth knows he must find his way out of the maze of his own psyche. In doing so, he will face the most difficult spiritual test of his life: to acknowledge the absolute truths—both good and bad—that have shaped his past, and that may be the only keys to his future.